Work Accident Risk Analysis Using Failure Mode and Effect Analysis (FMEA) Method at PT. XYZ - Dimasuharto, Nugroho; Hartelina, Hartelina; Nurhasanah, Nunung; Jajang Suyaman , Dede (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
In the production process, the interaction between humans and machines is closely related. From this the higher the risk of accidents along with the higher workload. This study aims to identify the risk of accidents that may arise during the work in progress. In addition, to identify actions that can be taken to reduce these risks. This type of descriptive qualitative research was conducted to assess the risk of work accidents at PT. XYZ. The data used in this study is primary data obtained through interviews using a questionnaire on one of the workers of PT. XYZ. The data were analyzed using the Failure Mode and Effect Analysis (FMEA) method to find the RPN and critical values ​​to find priority risks for action. The results obtained are that there are 4 work objects on the machine being analyzed, namely the stamping machine, lathe, welding machine, and milling machine. Based on the RPN value, it was obtained a value of 264 for a cut hand, 357 for a hand hit by a craft, 148 for a hand exposed to a welding spark, and 371 for a hand-carried by a machine. Based on the highest critical value, a stamping machine was obtained with a value of 66. The suggestion given to anticipate the occurrence of work accidents is by affirming SOPs in the use of Personal Protective Equipment (PPE), as well as workers' understanding of the risks of work accidents and their impacts.